CHANGES OF THE CARDIOVASCULAR SYSTEM STATE IN YOUNG MEN DEPENDING ON THEIR PSYCHOLOGICAL STATUS - Bilovol, O.M.; Kniazkova, I.I.; Mishchenko, V.M.; Golovachova, V.O.; Kuzminova, N.V.; Kryvoshapka О.V.; Abramova, L.P. (World of Medicine and Biology, 2024)
The purpose of the study was to establish the influence of the psycho-emotional state on clinical and hemodynamic parameters and the level of physical performance in young men. 82 young men (average age 28.4±5.2 years) without cardiovascular pathology and any somatic diseases in the anamnesis were examined. Depending on the psycho-emotional state, according to the anxiety questionnaire by Ch. D. Spielberg, the examined white men were divided into 2 groups: the main – with high anxiety – 43 people and the control – 39 people without violations of psycho-emotional status. It was established that young men without pathology of the cardiovascular system with a high level of anxiety according to the scale of Ch. D. Spielberg had reduced physical capacity according to the test with dosed physical load. It was determined that young men with reduced physical capacity and increased anxiety have a high prevalence of heart rhythm disorders according to daily ECG monitoring and signs of left ventricular diastolic dysfunction.